Photography as a treasury of literary metaphors in Nino Haratischwili’s novel Lack of Light - Ivanova, Ralitsa (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The everyday presence of visual media has long influenced human perception and led to shifts in the hierarchy of representation and communication forms. In the context of this visual turn, the present article focuses on the literary metaphorization of photography in Nino Haratischvili’s novel Lack of Light. Various metaphorical concepts of photography and their overlap with the techniques of restoration and drawing are discussed.